Correction: Tissue expression of antigens of ABH blood groups in species of New World Monkeys (Aotus infulatus, Callithrix jacchus, Sapajus apella and Saimiri sciureus). - Délia Cristina Figueira Aguiar (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pone.0241487.].